Structural enrichment reduces aggression in Tilapia rendalli - Torrezani, Camila Sobral [UNESP]; Pinho-Neto, Cândido Ferreira [UNESP]; Miyai, Caio Akira [UNESP]; Sanches, Fabio Henrique Carretero [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Taylor & Francis, 2013)
Environmental enrichment seeks to improve the behavior of captive animals. Few studies have developed enrichment strategies for fish, particularly for use in aquaculture. Environmental enrichment for territorial and aggressive animals has the potential to increase both the amount of defensible resources and the value of a disputed territory which can increase the level of aggression. This study evaluated this hypothesis for the redbreast tilapia, Tilapia rendaIli. We used a short-term approach for evaluation of fish aggressive behavior by recording it for 30 min after introduction of a pair of fish into each experimental aquarium. Our main finding was that the latency to start a fight was lower in an enriched environment, but the frequency of attacks was higher in a non-enriched environment (control). Furthermore, we observed clear hierarchical behavior (submissive dark stripes on the body and dominant light-colored bodies without stripes) only in the non-enriched environment. Structural enrichment of the environment for redbreast tilapia leads to decreased aggression and cohabitation without hierarchical dominance. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: aggressiveness; agonistic behavior; animal welfare; environmental complexity; fish; game theory; Tilapia rendalli; aggression; cohabitation; Animalia; Tilapia